2020
DOI: 10.1093/ehjcvp/pvaa067
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of direct oral anticoagulants vs. low molecular weight heparin for cancer-related venous thromboembolism: a meta-analysis of randomized trials

Abstract: Aims To examine the efficacy and safety of direct oral anticoagulants (DOAC) versus low molecular weight heparin (LMWH) in patients with cancer-related venous thrombo-embolism (VTE). Methods and Results An electronic search of MEDLINE, SCOPUS and COCHRANE without language restrictions was performed through April 2020 for randomized controlled trials that compared the effects of DOACs versus LMWH on patients with cancer-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…The results of the meta-analysis are consistent with those of previous meta-analyses of DOAC use in cancer patients that reported higher CRNMB [27], but similar major bleeding events [28,29] in DOAC users compared to those taking LMWH. Although major bleeding in the present metaanalysis was not signi cantly different between GI cancer patients receiving DOACs and GI cancer patients receiving LMWH, there was a trend towards increased major bleeding in the DOACs group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the meta-analysis are consistent with those of previous meta-analyses of DOAC use in cancer patients that reported higher CRNMB [27], but similar major bleeding events [28,29] in DOAC users compared to those taking LMWH. Although major bleeding in the present metaanalysis was not signi cantly different between GI cancer patients receiving DOACs and GI cancer patients receiving LMWH, there was a trend towards increased major bleeding in the DOACs group.…”
Section: Discussionsupporting
confidence: 87%
“…DOACs have become an alternative to LMWH for the treatment of CAT. Despite the non-inferior e cacy of DOACs to LMWH for preventing recurrent VTE, a higher bleeding risk was found in certain DOACs in a subgroup analysis of patients with GI and genitourinary tract cancers compared to that of LMWH [25][26][27]. However, previous randomized controlled trials enrolled patients with various kinds of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…At the time the search was ended (October 6, 2020), 46 records were identified, of which 26 were discarded on title and abstract ( n = 24) or full‐text ( n = 2). The 20 remaining meta‐analyses were published in nonpredatory peer‐reviewed journals: five studies pooled the data of two RCTs, 6‐10 four studies pooled the data of three RCTs, 11‐14 and 11 studies pooled the data of four RCTs 15‐25 . The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 20 remaining meta-analyses were published in nonpredatory peer-reviewed journals: five studies pooled the data of two RCTs, 6-10 four studies pooled the data of three RCTs, [11][12][13][14] and 11 studies pooled the data of four RCTs. [15][16][17][18][19][20][21][22][23][24][25] The main characteristics of the 20 meta-analyses are described in Table 1 and the results of the 20 meta-analyses for efficacy and safety endpoint are shown Figure 1. Within each category of meta-analysis (two, three, or 4 RCTs), the results were similar regarding the risks of VTE recurrence (differences in pooled relative…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…In recent years, with respect to DOACs vs LMWH, besides SELECT-D trial [ 37 ], six meta-analyses indicated that DOACs were more efficacious in the treatment of cancer-associated VTE with an increase of bleeding risk, compared with LMWH [ 11 , 20 , 38 41 ], whereas a retrospective study [ 7 ] and another five meta-analyses [ 10 , 15 , 16 , 42 , 43 ] indicated that DOACs were more efficacious with a comparable bleeding risk, compared with LMWH. In the ADAM VTE trial, major bleeding and VTE recurrence rates were both lower in cancer patients with VTE receiving oral apixaban than those receiving dalteparin [ 44 ].…”
Section: Comparison Among Different Therapeutic Anticoagulant Agentsmentioning
confidence: 99%